The Contribution Of Agricultural Sector Toward Gross Domestic Product (Case Study In China) - Tong, Shuai; Gunawan, Cakti Indra; Dyanasari (International Research & Development for Human Beings (IRDH), 2025)
The aim of research is 1) To assess the growth level of major agricultural products supporting China's GDP from 1989 to 2023. 2). To compare the performance of the agricultural sector with GDP through CAGR The analysis then continues to the comparison between CAGR rice, corn and wheat to CAGR GDP. Next, GDP predictions are made until 2050. The selection of 2050 is based on the reason to see the prediction of the next 25 years as the number of years that provide the possibility of many significant changes. The result of study shows Trend of agriculture towards GDP of China in the last 3 decades shows that, there is a declining in contribution of agriculture but it is still important Changes in economic growth in China from agriculture towards GDP is affected by the development of the industry, not the value of agriculture towards GDP.